Development and Initial Validation of a Scale to Measure Social Abuse in Intimate Partner Relationships - Park, Sihyun (Journal of interpersonal violence, 2025)
Social abuse represents a distinct form of intimate partner violence characterized by intentional violations of a victim’s social rights and inherent need to belong. This is achieved by tactics such as severing, interfering with, and surveilling the victim’s social connections as well as limiting their social participation. Such abuse often results in victims experiencing social isolation, potentially causing adverse mental health outcomes and failure to seek help. This study aimed to develop and validate the Social Abuse Scale (SAS) to measure social abuse in intimate partner relationships. After generating the preliminary items, content validity testing was performed. Ten international experts reviewed the items and assessed their relevance. Additionally, 17 interview participants assessed the items for clarity and ease of response. Thereafter, the SAS was administered to 251 individuals, either currently in or who had an intimate relationship in the previous year. The final SAS comprised 30 items unified under a single-factor structure, which accounted for approximately 69.77% of the total variance. Confirmatory factor analysis confirmed the model’s satisfactory fit. The instrument showed excellent internal consistency, as evidenced by Cronbach’s alpha and a McDonald’s omega value of .986. The SAS can be employed to investigate the prevalence of social abuse, its underlying mechanisms, and its impacts, and it can also assist in further development and evaluation of programs aimed at its prevention.